The geotouristic potential of the scenic underground routes in the “Wieliczka” and “Bochnia” Salt Mines (Carpathian Foredeep) - Dzięgiel, Maciej (Geotourism/Geoturystyka, 2023)
In this article, five scenic underground routes of historical salt mines in Wieliczka and Bochnia towns were the subject of comparative research, considered as very essential examples of geotouristic potential. In the “Wieliczka” Salt Mine, there are Touristic and Miners’ Routes, and in the “Bochnia” mine, there is a Multimedia Touristic route, as well as two Miners’: Natural and Historical ones.The routes lead through the parts of old mines. These salt deposits are a part of the Miocene evaporitic formations, as a fragment of the Carpathian Foredeep. A comparative geotouristic potential evaluation of all these routes was made to meet tourists’, educators’ and investors’ expectations and needs to raise their geotouristic development level. The statistical data of the annual number of visitors for the last few years at the described routes were also discussed. In general, interest in these routes has been growing, as the popularity of the industrial heritage in the “Wieliczka” and “Bochnia” Salt Mines has been regularly developing. They have become very widely known in Poland and around the world.